SARS-CoV-2 Spike-Specific CD4+ T Cell Response Is Conserved Against Variants of Concern, Including Omicron - Mazzoni, Alessio; Vanni, Anna; Spinicci, Michele; Capone, Manuela; Lamacchia, Giulia; Salvati, Lorenzo; Coppi, Marco; Antonelli, Alberto; Carnasciali, Alberto; Farahvachi, Parham; Giovacchini, Nicla; Aiezza, Noemi; et al. (Frontiers in Immunology, 2022)
Although accumulating data have investigated the effect of SARS-CoV-2 mutations on antibody neutralizing activity, less is known about T cell immunity. In this work, we found that the ancestral (Wuhan strain) Spike protein can efficaciously reactivate CD4+ T cell memory in subjects with previous Alpha variant infection. This finding has practical implications, as in many countries only one vaccine dose is currently administered to individuals with previous COVID-19, independently of which SARS-CoV-2 variant was responsible of the infection. We also found that only a minority of Spike-specific CD4+ T cells targets regions mutated in Alpha, Beta and Delta variants, both after natural infection and vaccination. Finally, we found that the vast majority of Spike-specific CD4+ T cell memory response induced by natural infection or mRNA vaccination is conserved also against Omicron variant. This is of importance, as this newly emerged strain is responsible for a sudden rise in COVID-19 cases worldwide due to its increased transmissibility and ability to evade antibody neutralization. Collectively, these observations suggest that most of the memory CD4+ T cell response is conserved against SARS-CoV-2 variants of concern, providing an efficacious line of defense that can protect from the development of severe forms of COVID-19.